Enhancing Direct Marketing and Loan Application Assessment Using Data Mining: A Case Study of Yaa Asantewaa Rural Bank Limited - Amponsah, Anokye Acheampong (2017)
A Thesis submitted to the Department of Computer Science, College of Science, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Philosophy,